Mapping of quantitative trait loci for antioxidant molecules in tomato fruit: Carotenoids, vitamins C and E, glutathione and phenolic acids. (March 2020) - Gürbüz Çolak, Nergiz; Eken, Neslihan Tek; Ülger, Mehmet; Frary, Anne; Doğanlar, Sami
Highlights: Assessment of breeding potential of Solanum pimpinellifolium for tomato antioxidants. Improvement of carotenoid and vitamin content in tomato with S. pimpinellifolium alleles. Identification and mapping of QTLs for antioxidants compounds. Identification of candidate genes for vitamin C, vitamin E and phenolic acids. Abstract: The nutritional value of a crop lies not only in its protein, lipid, and sugar content but also involves compounds such as the antioxidants lycopene, β-carotene and vitamin C. In the present study, wild tomato Solanum pimpinellifolium LA 1589 was assessed for its potential to improve antioxidant content. This wild species was found to be a good source of alleles for increasing β-carotene, lycopene, vitamin C and vitamin E contents in cultivated tomato. Characterization of an LA 1589 interspecific inbred backcross line (IBL) mapping population revealed many individuals with transgressive segregation for the antioxidants confirming the usefulness of this wild species for breeding of these traits. Molecular markers were used to identify QTLs for the metabolites in the IBL population. In total, 64 QTLs were identified for the antioxidants and their locations were compared to the map positions of previously identified QTLs for confirmation. Four (57 %) of the carotenoid QTLs, four (36 %) of the vitamin QTLs, and 11 (25 %) of the phenolic acid QTLs were supported by previous studies. Furthermore, several potential candidate genes were identified for vitamins C and E and phenolic acids loci. These candidate genes might be used as markers in breeding programs to increase tomato's antioxidant content.